Understanding families under economic and non-economic stress - Ang, Sheena Yue Ting (2011)
Despite the existence of an extensive welfare system, facilitated by government welfare schemes and many helping hands in the community, there are still about 90,000 to 100,000 families that require aid, including both immediate and long-term support. (Neo, 2009) This report seeks to examine the economic and non-economic stresses encountered by needy families, their causes and remedies. By conducting a survey with 200 targeted respondents comprising of the general public, individuals seeking help from Community Development Councils (CDCs) and Meet the people sessions (MPS), we hope to gain insight of the difficulties faced by low-income families, factors causing these stresses, social norms of helping the poor and the usefulness of government welfare schemes. 2 interviews are conducted with CDC Officer, Ms. Normalah and Director of Rotary Family Service Centre, Mr. Palani. With access to their experiences and perspectives, we hope to supplement our understanding of the stresses of needy families and their causes. Low income groups with high financial burden also tend to face high non-financial stress, yet these stresses are hard to resolve. Short term support is insufficient. Long term solutions, such as inducing the poor to be more conscientious in their efforts to better their lives and prompting the poor to be responsible for themselves through working are required. These could be done through more counseling and improvement in Work Support scheme. Effort has to be channeled into determining and improving solutions that are workable in reducing the number of people reliant on welfare.